Does Fasting and High-Fatty Diet Effect Ossseointegration: An Experimental Study - Kaya, Ca; Guler, R.; Yavuz, Mc; Ozcan, Ec; Bozoglan, A.; Dundar, S. (Wolters Kluwer Medknow Publications, 2025)
Background: Hyperlipidemia caused by a high-fat diet (HFD) has many adverse effects on the cardiovascular system, including vascular problems. In addition, a high-fat diet has significant adverse effects on bone health. Aim: This study aimed to investigate the levels of bone-implant connection in rats subjected to fasting and a high-fatty diet. Methods: This study utilized a sample size of 28 female Spraque-Dawley rats. The rats were divided into four groups, with 7 rats in each group; the control group on a normal diet (Group 1) (n = 7), the fasted group (Group 2) (n = 7), the high-fatty diet (HFD) group (Group 3) (n = 7), and the fasted and high-fat diet (Group 4) (n = 7). Machined surfaced titanium implants with a diameter of 2.5 mm and a length of 4 mm were placed in the right tibia bones of the subjects. All rats that continued the administered diet for 12 weeks were sacrificed at the end of the experimental period. The implants and the surrounding bone tissue were surgically removed and subjected to biomechanical analysis to assess bone-implant osteintegration. Results:There was no statistically significant difference in bone-implant osteointegration (P > 0,05) between the rats in the control group and the other three groups. Conclusion:This study determined that fasting or maintaining a high-fat diet does not adversely affect the bone-implant connection in rats' tibias.
Keywords: Fasting; high-fatty diet; implant; osteointegration